Cruise destination attributes: measuring the relative importance of the onboard and onshore aspects of cruising. Issue 4 (2nd October 2018) - Whyte, Lincoln James; Packer, Jan; Ballantyne, Roy
ABSTRACT: Cruise tourism is an increasingly popular and profitable industry where cruise lines have positioned the cruise ship as the focal point of a vacation. This has led to speculation regarding the relative importance of the ship and the ports of call as the primary destination of cruise tourism. This issue has implications for the decision-making process of cruise travellers, as well as cruise marketing, itinerary planning, shore excursions and ship design. This study introduces the concept of co-destination and develops a new quantitative measurement scale for cruise destination attributes that separates onboard (ship) and onshore (ports of call) components. This instrument makes it possible to measure the relative importance of the onboard and onshore aspects in the decision-making process. Results confirm the scale's ability to reliably and accurately measure cruise destination attributes and answers the question of whether passengers perceive the cruise or the ports of call to be the primary destination.